PENGARUH METODE SAVING MATRIX TERHADAP PENENTUAN RUTE PERGESERAN DISTRIBUSI LOGISTIK PADA KORBAN BENCANA GEMPA BUMI DI CIANJUR - Agustina Dwi MP; Bima, Daniar (JURNAL DWIJA KUSUMA, 2025)
Disaster management of the earthquake in the Cianjur region, the logistics distribution process plays a crucial role in route selection. This is important to ensure that logistics reach the right destination promptly, which can help save time and distribution costs. However, factors such as terrain and weather greatly affect the determination of logistics distribution routes. In this case, Yon Bekang 1 Kostrad/TBY is responsible for distributing logistics in the earthquake disaster area in Cianjur, delivering supplies to evacuation points based on the number of disaster victims. The method used for determining the distribution route is the saving matrix. This method aims to reduce distance, time, fuel consumption, and costs. The saving matrix method works by combining two routes into one distribution trip to achieve savings in distance, time, fuel, and costs. The results of this study indicate that the saving matrix method can reduce fuel costs by up to 19.7% (Rp 71,000) per trip and minimize the travel distance by up to 17% (22 km).